The Tetraspanin CD151 in Papillomavirus Infection - Konstanze D. Scheffer (Viruses, 2014)
Human papillomaviruses (HPV) are non-enveloped DNA tumor viruses that infect skin and mucosa. The most oncogenic subtype, HPV16, causes various types of cancer, including cervical, anal, and head and neck cancers. During the multistep process of infection, numerous host proteins are required for the delivery of virus genetic information into the nucleus of target cells. Over the last two decades, many host-cell proteins such as heparan sulfate proteoglycans, integrins, growth factor receptors, actin and the tetraspanin CD151 have been described to be involved in the process of infectious entry of HPV16. Tetraspanins have the ability to organize membrane microdomains and to directly influence the function of associated molecules, including binding of receptors to their ligands, receptor oligomerization and signal transduction. Here, we summarize the current knowledge on CD151, and CD151-associated partners during HPV infection and discuss the underlying mechanisms.